Do Pocinho Cabeças: a televisão pelo olhar das crianças de Ouro Preto - Claudio Marcio Magalhaes (2005)
Researches in Brazil in the world say that children see TV, in media, three to five hours for day. Time much more that they stay in school or another activities. And sufficient time to be a social relationships between child and TV, that dont only between bolt, but with everything around them, where they are. With help to another similar researches and views of Vigotski, Bakthin e Charlot, the target is discovery a little more about this relationships, just it a researcher object. It is from the children views, training separate to adults views about what they think to be child. For that, we was 21 jobs in three class in high school, with children of 9 and 10 years-ago, in Ouro Preto, small city in the state Minas Gerais, in central of Brazil, in two school, one private school to media class and another public school and peripheral care community. Beware the exercises in the class, the 62 children that participates was little TVs notebooks for to be notes and write them personal impressions. The child that see in the end é a active cultural person, in more part of time with condition to understand and get what is good and bad in yours relationship with TV. But this child is, too, knower that your fragile condition, that she or he want references and limits, that they like of TV like the adults, but they love more them parents.